STRUCTURAL RECONSTRUCTION AND PALEOGEOGRAPHY IN PALEOGENE, OFFSHORE EASTERN OF MADURA ISLAND, EAST JAVA BASIN - Mubin, Fathul
The East Java Basin is one of the major hydrocarbon potential basins in Indonesia. However, understanding of the tectonic development of the area is still subject to ongoing discussion. Detailed regional geologic investigation was carried out to study and evaluate tectonic history and basin development in relation to hydrocarbon potential of the area. Previous studies have found indications of early Paleogene sediment in limited number of wells in the eastern part of the East Java Basin. Hydrocarbon potential shown by some of these wells in Paleogene interval opens the possibility to explore hydrocarbon potential in the early Cenozoic era associated with tectonic events at that time. The study was conducted using 2D seismic which is many and dense (286 lines) and 14 digital wells in this area to determine the top horizon continuity of syn-extension unit in early Paleogene (Pre-Ngimbang and Ngimbang Formation) and other top horizon units. The palinspastic method was conducted to validate the geometry of geological structure and deformation history. These methods are expected to determine the distribution of sediment deposits in early Paleogen (Pre-Ngimbang and Ngimbang Formations) and tectonic evolution that occurred at that time. The results of this study indicate that Pre-Ngimbang Formation consists of sandstone, shale and coal deposits at Paleocene, and only limitedly distributed in the eastern part of the study area, it is possible to continue to east of this area. The Ngimbang Formation consists of sandstone, shale and limestone in Middle Eocene - Late Eocene spread over the study area. Both are post-collision sediments. Pre-Ngimbang Formation (syn-extension I) and Ngimbang Formation (syn-extension II) are deposits in the extension phase that strated 65 years ago with a rollback mechanism due to the rotation of Sundaland. The rollback mechanism has reactivated the east-west structures pattern to becomes accommodation spaces for sediment at early Paleogene.